Total Productive Maintenance and the Impact of Each Implemented Pillar in the Overall Equipment Effectiveness - José Carlos Meca Vital; Carlos Roberto Camello Lima (International Journal of Engineering and Management Research, 2020)
Total Productive Maintenance (TPM) focuses on maximizing equipment performance, establishing a productive maintenance system that optimizes its life cycle, contributing for the continuous improvement and availability, avoiding early equipment wear, being necessary that the maintenance works on preventing with managerial focus. In this study, the impact of each implemented TPM pillar in the Overall Equipment Effectiveness (OEE) metric was analyzed, evaluating the performance resulting from each implemented pillar. The approach of the research is predicated on the Survey method, based on the intentional sample of the industrial companies in Brazil, which implemented the method. The results evidenced that the Focused Improvement and Planned Maintenance pillars were implemented in most of the respondent companies, being part of different segments, such as metallurgical, food, textile, auto-parts, household appliances, school material, automobile and chemical products. The OEE metric showed the TPM evolution comparing the result at the beginning of the implemented activities and at the end. Other important observation was in the implementation of the pillars, when compared with the suggested literature, a change of priority and sequence occurred. The Autonomous Maintenance pillar was suggested as the second pillar to be implemented. It is implemented only after the Training and Education pillar, which is the fourth suggested pillar. The other pillars were implemented in the original sequence indicated by literature.